2017
DOI: 10.1002/cam4.1187
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profiles of hematopoietic stem and progenitor cells from patients with chronic myeloid leukemia: the effect of in vitro culture with or without imatinib

Abstract: In this study, we determined the gene expression profiles of bone marrow‐derived cell fractions, obtained from normal subjects and Chronic Myeloid Leukemia (CML) patients, that were highly enriched for hematopoietic stem (HSCs) and progenitor (HPCs) cells. Our results indicate that the profiles of CML HSCs and HPCs were closer to that of normal progenitors, whereas normal HSCs showed the most different expression profile of all. We found that the expression profiles of HSCs and HPCs from CML marrow were closer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Transcriptional changes taking place at CML were identified by means of differential gene expression analysis, accounting for confounding factors. These analyses revealed deregulation of genes reported to be altered in previous CML investigations, such as RXFP1, 43 PIEZO2, 55 and CD26, 56 and in leukemia studies, such as CD69, 57 ST18, 58 and MUC4. 59 Expression analysis also suggested that DNA damage could be related to the downregulation of DNA-repair machinery genes and that dysregulation events in genes, including DNMT1, 60 SEPP1, 61 NEIL1, 62 and WT1, 63,64 may have contributed to the high occurrence of DNA damage-associated variants in our cohort.…”
Section: Discussionmentioning
confidence: 66%
“…Transcriptional changes taking place at CML were identified by means of differential gene expression analysis, accounting for confounding factors. These analyses revealed deregulation of genes reported to be altered in previous CML investigations, such as RXFP1, 43 PIEZO2, 55 and CD26, 56 and in leukemia studies, such as CD69, 57 ST18, 58 and MUC4. 59 Expression analysis also suggested that DNA damage could be related to the downregulation of DNA-repair machinery genes and that dysregulation events in genes, including DNMT1, 60 SEPP1, 61 NEIL1, 62 and WT1, 63,64 may have contributed to the high occurrence of DNA damage-associated variants in our cohort.…”
Section: Discussionmentioning
confidence: 66%
“…Given the high number of cancer types exhibiting a coordinated expression decrease (or increase) of these core secretome genes, we reasoned that these genes would likely be responsible for important tumor-specific functions. Many of the genes exhibiting decreased expression are putative or established tumor suppressors (e.g., ANGPTL1, C2orf40, CHRDL1, OGN, C7, GREM2) ( Hu et al, 2018 ; Kuo et al, 2013 ; Li et al, 2015 ; Pei et al, 2017 ; Tsubamoto et al., 2016 ; Ying et al, 2016 ), are involved in the remodeling of the extracellular matrix (ECM) (e.g., DNASE1L3, CLEC3B, PI16, CCBE1) ( Barton et al, 2010 ; Hawes et al., 2015 ; Hazell et al, 2016 ; Obrist et al, 2004 ), and/or participate in cell-matrix adhesion functions (e.g., MFAP4, DPT, MAMDC2) ( Avilés-Vázquez et al, 2017 ; Pilecki et al, 2016 ; Yamatoji et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since separase cleaves cohesin complexes that hold sisterchromatids together and has been reported to be involved in controlling replication fork dynamics and higher order chromatin architecture, we set out to investigate the replication fork speed in H-and L-fractions by the DNA fiber technique [40,41]. Replication fork speed may directly influence proliferation and cell doubling time but may also contribute to genomic instability via replication stress [42] and to altered interphase DNA repair [22], both phenomena potentially contributing to disease progression in CML [46]. We have performed pulse chase CIdD/IdU incorporation experiments on Gating strategy for sorting separase-active CD34 + cells into fractions with high (H-fraction) and low (regular, L-fraction) separase proteolytic activity.…”
Section: Cd34 + Cells With High Separase Activity Levels (H-fractionsmentioning
confidence: 99%